OCORRÊNCIA DE ANTICORPOS ANTI-NEOSPORA CANINUM EM BOVINOS LEITEIROS E DE CORTE DA REGIÃO DE PRESIDENTE PRUDENTE, SP - Sartor, I. F. [UNESP]; Garcia, A. [UNESP]; Vianna, L. C. [UNESP]; Pituco, E. M.; Dal Pai, V.; Sartor, R. (Instituto Biológico, 2022)
Neospora caninum is considered one of the most important world wideagents that affect the bovine reproductive tract. In Brazil the initial studies of this infection were based on regional soroepidemiologic data. So, blood serum samples of 505 Nelore beef cattle and 408 of Holstein dairy cattle located in the region of Presidente Prudente, SP, Brazil were analysed using the immunoenzymatic ELISA test. The occurrence of antibodies anti-Neorospora caninum for dairy cattle was 35.54% (145/408) and 20.0% (101/505) for the beef cattle. The analysis of the results revealed evidence of N. caninum infection in the herds of this region, which was significatively higher in dairy cattle (p < 0.01).

O Neospora caninum é considerado um agente de prioridade de estudo em reprodução animal em todo mundo, pelos distúrbios reprodutivos que afetam os bovinos. No Brasil, os estudos iniciais desta infecção são baseados em levantamentos soroepidimeológicos regionais. Sendo assim, amostras de soros sanguíneos de 505 de bovinos de corte da raça Nelore e de 408 bovinos leiteiros da raça Holstein localizados na região de Presidente Prudente, SP, Brasil, foram analisadas pelo teste imunoenzimático (ELISA). A ocorrência de anticorpos anti-N. caninum para o gado leiteiro foi de 35,54% (145/408) e 20,0% (101/505) para o gado de corte. A análise dos resultados mostra que há evidência de infecção de N. caninum nos rebanhos da região, sendo a ocorrência significativamente maior em rebanhos leiteiros (p < 0,01).
OCCURRENCE OF ANTIBODIES ANTI-NEOROSPORA CANINUM IN DAIRY AND BEEF CATTLE IN THE REGION OF PRESIDENTE PRUDENTE, SP, BRAZIL
Keywords: Neosporosis; occurrence; Nelore; soroedpidemiology; Holstein; Nelore Holstein; cattle; Brazil; Neosporose; ocorrência; soroepidemiologia; Nelore; Holandês; bovino; Brasil